Financing and Tax Factor in the Agricultural System of Azerbaijan - Girkhlarov, E. (Економічний вісник Донбасу, 2022)
In Azerbaijan, as in the rest of the world, agriculture is mainly financed from the state budget, and many taxes and other benefits are provided in this area. The main reasons for tax and other benefits in agriculture are to create conditions for the development of this sector in the country, to ensure food security within the country, to minimize imports in this area, and so on. Depending on the factors, serious problems arise and their solution is one of the serious issues facing the state and relevant agencies. В Азербайджані, як і в усьому світі, сільське господарство в основному фінансується з державного бюджету, і в цій сфері передбачено багато податків та інших пільг. Основними причинами надання податкових та інших пільг у сільському господарстві є створення умов для розвитку цієї галузі в країні, забезпечення продовольчої безпеки всередині країни, мінімізація імпорту в цій сфері тощо. Залежно від чинників виникають серйозні проблеми, вирішення яких є одним із серйозних завдань держави та відповідних органів.